Penerapan Perjanjian bagi Hasil terhadap Pengelolaan Bersama Lahan Budidaya Tambak - Sulistyowati, Eny; Masnun, Muh Ali; Nugroho, Arinto; Hikmah, Nurul; Wardhana, Mahendra (University of Merdeka Malang, 2019)
The researchers are interested in analyzing the application of how profit sharing agreements are related to guarantee legal certainty and justice for owners, tenants and cultivators of cultivated land. This study uses non-doctrinal research (socio legal), primary data and secondary data used in analyzing problems. The application of the production sharing agreement between the owner, tenant and cultivator of ponds cultivation land in Gresik Regency has not been implemented as stipulated in the Fishery Product Sharing Law. The agreement made, is still in the form of not written, but in oral form that has occurred from generations before them and until now. In terms of the application of the timeframe of the production sharing agreement in Gresik Regency it is still not in accordance with the Fishery Production Sharing Law (specifying a minimum of 3 years and 6 seasons), this is based on the profit sharing agreement that is carried out uncertainly for how many years / how many seasons. In terms of the risk of crop failure, it still does not represent justice.How to cite item:Â Sulistyowati, E., Masnun, M., Nugroho, A., Hikmah, N., Wardhana, M. (2019). Penerapan Perjanjian bagi Hasil terhadap Pengelolaan Bersama Lahan Budidaya Tambak.Â Jurnal Cakrawala Hukum, 10(2), 187-197. doi:https://doi.org/10.26905/idjch.v10i2.3365